Hábitos de higiene bucal e a utilização dos serviços odontológicos em escolares - Zambaldi, Maiara Paula Malacarne (2016)
This study evaluates the factors related to oral hygiene habits and the use of dental services in students aged seven to 10 years in the city of Vitória- Espírito Santo (ES). It is a cross-sectional study with a probabilistic sample of triple stage with final study population of 1282 children. Data were collect using a questionnaire applied to the children and a questionnaire sent to parents to fill out and return. Multivariate Regression Logistics analyses were conduct between children’s, maternal and socioeconomic characteristics with the outcome related to own a toothbrush and dental appointment once in a lifetime determinants of access to dental health services. Multinomial Regression Multivariate analyses also tested combinations between the three possible situations of oral health practices: less favorable level, intermediate level and more favorable level with children’s, maternal and socioeconomic characteristics. The results showed that the study population was composed mostly by women 744 (58.0%), aged eight 359 (28.0%) and nine years 360 (28.1%) and enrolled in the public school system 1061 (82.8%). In the final model of Logistic Regression, the variables that remained associated with own a toothbrush were ages of eight, nine and 10 years old; maternal smoking and dental appointment once in a lifetime. To the variable dental appointment once in a lifetime, the associated variables were ages of nine and 10 years old; type of school; number of rooms and own a toothbrush. In Multinomial Regression model, the associated variables were birth weight, living with father and mother in the same home, dental appointment once in a lifetime, cavity experience and own a toothbrush. This study proven that socio-economic and individual factors are related with access and oral health habits.